The role of communication in enterprise system implementation - Sedmak, Melissa (Cranfield University, 2006)
The research efforts up to date have not been directed towards the study of the role of communication during an implementation of an enterprise system. However, some efforts are noted which stress communication as a critical factor and a problem in general during the implementation. During the scoping phase of this research, communication was proved to be of significance as a process in the realisation of embedding of an enterprise system into the business. Considering the complexity of an implementation of a system and consequently the complexity of its study, the research method based on processual approach was developed to enable a better understanding of the dynamics of this process. Three case studies have been conducted with the focus on the understanding of the role and significance of communication. They included interviews with the employees involved in the project or affected by the new system: project managers, top managers, system specialists, and users. The findings focus on the elements important to realise the communication process: communication strategy, management activities such as announcements, motivation to communicate, resources such as time, how informed the people who are involved are, communication across the project, communication structure and process, facilitators as people who enable the communication process, and communication about the technical issues. Special focus was on the effect of communication on the transfer of psychological ownership of the system, concerns about change and employee commitment. Additionally, several themes are found to affect communication. These are: organisational structure, team cohesion and trust. The role of communication confirms that all the parties need to use the same language to enable common understanding. The communication process is found to have direct and indirect influence on development of common organisational goals, positive attitude towards the new system, and embedding of the new system in current organisational functioning.